Dewetting of Ni silicide thin film on Si substrate: In-situ experimental study and phase-field modeling. (15th January 2022) - Gao, Jianbao; Malchère, Annie; Yang, Shenglan; Campos, Andrea; Luo, Ting; Quertite, Khalid; Steyer, Philippe; Girardeaux, Christophe; Zhang, Lijun; Mangelinck, Dominique
Abstract: In this paper, the in-situ Scanning Electron Microscopy ( in-situ SEM) technique and three-dimensional (3-D) phase-field simulation were combined to perform a comprehensive study on the kinetics and mechanisms of dewetting (or agglomeration) of a 30 nm NiSi films on Si(100) substrate at 600 °C. The evolution of texture during agglomeration of the polycrystalline NiSi thin film was also studied by ex-situ Electron BackScattered Diffraction (EBSD). The phase-field simulation results showed that abnormal grain growth plays an important role in the dewetting process of polycrystalline films, while the misorientations between the NiSi grains and the Si substrate are the main reason for the agglomeration of NiSi polycrystalline thin film on the monocrystal Si substrate. Moreover, 3-D phase-field simulations coupled with experimental information on misorientation distribution and initial grain size were also performed, and the simulated Ni silicide grain morphology is in good agreement with the in-situ SEM results during agglomeration. In order to slow down or to suppress the agglomeration, it is highly recommended to increase the volume fraction of low angle grains, and/or to decrease the misorientation between the NiSi grain and the Si substrate or between the NiSi grains. Graphical abstract: Image, graphical abstract